2007
DOI: 10.1007/s10517-007-0139-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of recombinant interleukin-5, interleukin-3, and eotaxin on apoptosis in eosinophilic granulocytes

Abstract: We studied in vitro effects of recombinant interleukin-5, interleukin-3, and eotaxin on programmed death of eosinophils from healthy donors and patients with non-Hodgkin's lymphomas associated with severe blood eosinophilia. Interleukin-5 and eotaxin produced the most potent antiapoptotic effect on eosinophils from healthy donors. In patients with non-Hodgkin's lymphomas, spontaneous apoptosis in eosinophilic leukocytes was low and remained unchanged during incubation with recombinant proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…A possible mechanism underlying the blockade of glucocorticoid-induced apoptosis by recombinant IL-2 is its capacity to initiate the proliferative cascade by JAK/STAT, PI3K, or MAPK signal pathways converging on the regulation of the expression of bcl-2 gene; up-regulation of bcl-2 gene expression results in cell survival and proliferation [6]. This assumption is confi rmed by a well-known capacity of glucocorticoids to inhibit the synthesis of antiapoptotic [2] and stimulate the synthesis of proapoptotic Bcl-2 family proteins [6,15], which leads to activation of the apoptotic program in the cell [11]. Moreover, we previously showed that binding of STAT5 and AP 1 proteins activated by IL-2 to glucocorticoid receptor prevents the formation of complexes of these receptors with cofactors CBP/ p300 or SRC-1a, which blocks the transduction of the proapoptotic signal [3] Mitochondrial factors (cytochrome C, AIF, calcium ions, Apaf-1, etc.)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible mechanism underlying the blockade of glucocorticoid-induced apoptosis by recombinant IL-2 is its capacity to initiate the proliferative cascade by JAK/STAT, PI3K, or MAPK signal pathways converging on the regulation of the expression of bcl-2 gene; up-regulation of bcl-2 gene expression results in cell survival and proliferation [6]. This assumption is confi rmed by a well-known capacity of glucocorticoids to inhibit the synthesis of antiapoptotic [2] and stimulate the synthesis of proapoptotic Bcl-2 family proteins [6,15], which leads to activation of the apoptotic program in the cell [11]. Moreover, we previously showed that binding of STAT5 and AP 1 proteins activated by IL-2 to glucocorticoid receptor prevents the formation of complexes of these receptors with cofactors CBP/ p300 or SRC-1a, which blocks the transduction of the proapoptotic signal [3] Mitochondrial factors (cytochrome C, AIF, calcium ions, Apaf-1, etc.)…”
Section: Resultsmentioning
confidence: 99%
“…This mechanism limits the immune response after death of the pathogen. Apoptosis of T cells can be reduced or abolished by cytokines, whose receptors have common γ-chain (IL-2, IL-4, IL-7, IL-15, and IL-21) [2]. Excessive antigenic stimulation leads to antigen-induced apoptosis of T cells.…”
mentioning
confidence: 99%